PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2010-2012 (Students' Journal of Accounting and Banking, 2014)
The company's goal is to optimize the long -term value of the company. This study aimed to examine the effect of investment decisions, financing decisions, dividend policy, profitability, firm size on firm value. This study uses secondary data from annual reports obtained from BEI corner, www.bapepam.go.id and www.idx.co.id as well as from the Indonesian Capital Market Directory (ICMD). The samples were selected using purposive sampling technique to the study period 2010-2012. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing showed that (1) the investment decision has a positive effect on firm value. (2) The decision of funding has a positive effect on firm value. (3) the dividend policy has no effect on firm value. (4) Profitability positive and significant effect on firm value. (5) Firm size has no effect on firm value. Keywords: investment decisions, financing decisions, dividend policy, profitability, firm size and firm value